Organic Unities: A Response to the Problem of Evil - Floyd, Graham (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2019)
The principle of organic unities is a metaphysical claim regarding the nature of moral value. It states that the value of the whole is not equal to the summation of its parts. Even though this principle has a major impact on moral theory, it has been neglected in the consideration of the problem of God and evil. I claim that the theist can utilize the principle of organic unities to undermine the problem of evil. First, I explain the principle of organic unities and how it affects one’s understanding of moral value. Next, I explicate the two major historical versions of the problem of evil: the logical argument from evil and the evidential argument from evil. Lastly, I argue that the principle of organic unities demonstrates that God may logically co-exist with evil and that the atheologian lacks rational warrant appealing to gratuitous evil against God’s existence. As a result, both problems fail.